Lack of estrogen down-regulates CXCR4 expression on Treg cells and reduces Treg cell population in bone marrow in OVX mice - Fan, X-L; Duan, X-B; Chen, Z-H; Li, M; Xu, J-S; Ding, G-M (Cellular and Molecular Biology, 2015)
Postmenopausal osteoporosis (PMO) is the most common metabolic bone disease in women after menopausal. Recent works focused on cross-talk between immune regulation and bone metabolism pathways and suggested Treg cells suppressed bone resorption and osteoclasts (OC) differentiation in bone marrow via cell-cell contact interaction and/or secreting of IL-10 and TGF-beta. In this study, we investigated the impact of estrogen on regulatory T cells (Treg cells) trafficking and staying in bone marrow and we found that a significant reduction of Treg cell population in bone marrow in estrogen deficiency ovariectomied (OVX) mice. We then studied the expressions of chemokines CXCL12/CXCR4 axes, which were critical to Treg cells migration and our data show the expression of CXCR4 on Treg cells was relative with oestrogen in vivo, however, the expression of CXCL12 was not. Furthermore, the loss of trafficking ability of Treg cells in OVX mice was recoverable in our system. These findings may mechanistically explain why Treg cells lose their suppressive functions on the regulation of OC cells and demonstrate a previously unappreciated role for estrogen, which may be critical to the novel therapy in clinical practice of PMO patients.